Efficient recovery and enrichment of infectious rotavirus using separation with antibody-integrated graphite-encapsulated magnetic nanobeads produced by argon/ammonia gas plasma technology - Yamashiro R (Dove Medical Press, 2019)
Risa Yamashiro,1 Akikazu Sakudo,1 Masaaki Nagatsu2 1Laboratory of Biometabolic Chemistry, School of Health Sciences, University of the Ryukyus, Nishihara, Okinawa 903-0215, Japan; 2Research Institute of Electronics, Shizuoka University, Hamamatsu, Shizuoka 432-8561, Japan Background: Rotavirus is the representative cause of severe acute gastroenteritis in young children. A characteristic feature of rotavirus is low infectious dose and robustness of the virion, suggesting sanitation and hygiene will have little impact. Thus, development of a vaccine should be given priority. Efficient capture of infectious viruses is an important step in generating a vaccine. Previously, antibody-integrated magnetic nanobeads (MNBs) have been developed for virus capture. This study examines the applicability of this method for infectious rotavirus recovery and enrichment.Materials and methods: Graphite-encapsulated MNBs were treated with radio frequency (RF) excited Ar/NH3 gas mixture plasma to introduce amino groups onto their surfaces. Rotavirus viral protein 7 (VP7) antibody was attached to the surface of MNBs via these amino groups using a coupling agent, N-succinimidyl 3-(2-pyridyldithio)propionate (SPDP). The antibody-integrated MNBs were incubated with rotavirus-infected cell lysate and then separated from the supernatant by applying a magnetic field. After thorough washing, rotavirus was recovered and enrichment analysis done by polymerase chain reaction (PCR), immunochromatography, and an infection analysis using MA104 cells.Results and discussion: Immunochromatography and PCR indicate that anti-rotavirus antibody-integrated MNPs efficiently capture rotavirus with the capsid protein and viral RNA. The estimated recovery rate was 80.2% by PCR and 90.0% by infection analysis, while the concentrating factor was 7.9-fold by PCR and 6.7-fold by infection analysis. In addition, the absence of non-specific binding to the antibody-integrated MNPs was confirmed using anti-dengue virus antibody-integrated MNBs as a negative control.Conclusion: These results suggest that this capture procedure is a useful tool for recovery and enrichment of infectious rotavirus. Moreover, when combined with a suitable virus assay this capture procedure can increase the sensitivity of rotavirus detection. Therefore, this capture method is a valuable tool for generating vaccines as well as for developing sensitive detection systems for viruses. Keywords: rotavirus, antibody-integrated, magnetic beads, nanobeads, nanoparticle